Manejo comunal de fauna silvestre en el parque nacional cordillera azul, San Martín - Perú - Watanabe Sato, Jorge (2017)
Located between the rivers Huallaga and Ucayali, the National Park Blue Mountain range, was established the 2001, including more than 1.3 million hectares. In order to initiate the development of the program and its activities, revisions of information were made previously, like the obtained one from the Mapeo de Usos and Fortalezas (MUF), of investigations uses of resources developed in the zone of damping of the park and the local reality of the involved communities. In this first year of handling, the program is developed with the participation of two sectors, these are Shamboyacu and Pikiyacu, in addition important advances in the sectors of Chazuta, Cushabatay and to a lesser extent in the sector of Pucayacu were had. The process of the handling program presented displayed the following steps: 1) evaluation, 2) compilation and basic analysis of information, 3) design, 4) identification of users and areas of use, 5) elaboration of the use norms, 6) elaboration of the proposal of the communal handling, 7) implementation of the handling activities, 8) monitored of the process and, 9) analysis of the results. One hopes that the park and the zone of damping could be known by agricultura, sino también por actividades de caza, pesca y extracción maderera como una manera de subsistencia.